Microbial immigration in wastewater treatment systems: analytical considerations and process implications. (June 2019) - Frigon, Dominic; Wells, George
Graphical abstract: Highlights: Immigration is needed to adequately predict several aspects of WWTP processes. Classification of immigration analyses: diffusive (rare) and mass flow (observable). Heterotrophs are strongly selected between wastewater influent and activated sludge. Heterotrophs should be subdivided in several functional guilds. Nitrifiers' immigration appears neutral when comparing influent and mixed liquor. Abstract : Microbial immigration from sewers to wastewater treatment systems is attracting increasing attention for understanding community assembly mechanisms, and improving process modeling and operation. While there is no consensus on approaches to analyze immigration, we suggest to classify them as relevant to either rare (non-observable) diffusive immigration or to time-continuous high-rate mass flow immigration (i.e. mass effects). When analyzed by a mass flow approach, heterotrophs appear to be strongly influenced by deterministic selection, suggesting that the heterotrophs should be subdivided into several functional guilds when assessing their assembly mechanisms. Conversely, nitrifiers appear to transfer neutrally from sewer to activated sludge, and this immigration can restore full nitrification in otherwise non-nitrifying reactors. With further refinement, these findings could be included in predictive process models with various objectives.